2014
DOI: 10.1002/erv.2289
|View full text |Cite
|
Sign up to set email alerts
|

Binge Eating in Interview Versus Self‐Report: Different Diagnoses Show Different Divergences

Abstract: The findings have important clinical and theoretical implications and suggest that BE assessment is more complex than previously believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…This finding is different from other studies [Rhodes et al, 1995;Steketee et al, 1996], which observed greater reporting of urinary symptoms or obsessive compulsive symptoms in self-administered methods than in interviews. In another study of binge eating, the two methods showed the opposite direction in reporting depending on the subjects' diagnosis [Birgegård et al, 2014]. Further evaluation is needed identify the impact of the methods on our study findings.…”
Section: Discussionmentioning
confidence: 71%
“…This finding is different from other studies [Rhodes et al, 1995;Steketee et al, 1996], which observed greater reporting of urinary symptoms or obsessive compulsive symptoms in self-administered methods than in interviews. In another study of binge eating, the two methods showed the opposite direction in reporting depending on the subjects' diagnosis [Birgegård et al, 2014]. Further evaluation is needed identify the impact of the methods on our study findings.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, Pel aez-Fern andez et al 9 compared two different designs (single-stage versus two-stage) to assess the prevalence of ED among 559 males and females (14-18 years). 104 Nonetheless, self-report assessments are limited by their inability to determine formal ED diagnoses, and in clarifying complicated terms such as overeating. Although only trending towards statistical significance (P 5 0.06), these results highlight the likelihood of attaining higher prevalence rates using self-reports compared to two-stage approaches, and are in line with the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Such replications are important in psychological research to identify reliable findings (Koole & Lakens, 2012) and to generalize to clinical populations. Studies show that interview methods are a more reliable means of assessing eating disorder pathology (Birgegård, Norring, & Clinton, 2014). More commonly, studies with clinical samples tend to suffer from small sample sizes, which limit the reliability of conclusions.…”
Section: Discussionmentioning
confidence: 99%